QATAR 2022 FIFA WORLD CUP: MULTI-CULTURALISM OR CLASH OF CIVILIZATION - BALARABE ABUBAKAR BELLO; TUKUR ABDULKADIR (International Studies Journal)
This paper examines FIFA World Cup 2022 in Qatar in order to ascertain whether the event will promote multiculturalism or lead to a clash of civilizations. Qatar is the host nation for the 2022 FIFA World Cup and is a relatively small, but wealthy nation located in the Middle East, and is home to a diverse array of ethnic and cultural groups. The paper will analyze the potential benefits Qatar may gain in hosting the 2022 FIFA World Cup and how these benefits may lead to increased multiculturalism in the region. Additionally, the paper will examine the potential for the event to lead to a clash of civilizations, and the implications that could have. The Theory of Cultural Pluralism was adopted to serve as a theoretical base for this paper. The paper adopts qualitative analysis to serve as a method for data collection; it draws on a variety of research sources, including academic journals, news articles, and reports from international organizations. Overall, this paper assess Qatar’s motives for hosting the event, the potential for increased multiculturalism, the potential for a clash of civilizations, and the potential implications for human rights in the region.